MARGINALISASI PEREMPUAN DALAM PROBLEMATIKA LEGALITAS NIKAH SIRI DI INDONESIA - Asman, Asman (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2024)
This study discusses the marginalization of women in unregistered marriages. Unregistered marriages can cause polemics in society. Unregistered marriages referred to here are marriages that are considered legitimate, on the other hand unregistered marriages are also debated in the eyes of the law both in Islamic law and national law, because unregistered marriages are not registered by the state and do not meet the requirements and pillars of marriage that have been determined in Islamic law and Indonesian marriage law. This research method uses a qualitative literature type while the approach in this study is a normative approach. The focus of this study is how marginalization occurs against women in unregistered marriages from an Islamic legal perspective. The results of this study are that unregistered marriages are clearly not legally administrative and not all husbands and wives have marriage certificates because they are not registered by the state. In the case of unregistered marriages, the government does not provide a copy of the marriage certificate for couples who are married unregistered, which is proof of marriage that is registered by the state by the KUA